Functional Equivalence of Imagined vs. Real Performance of an Inhibitory Task: An EEG/ERP Study - Galdo-Alvarez, Santiago; Bonilla, Fidel M.; González-Villar, Alberto J.; Carrillo-de-la-Peña, María T. (Frontiers in Human Neuroscience, 2016)
Early neuroimaging and electrophysiological studies suggested motor imagery recruited a different network than motor execution. However, several studies have provided evidence for the involvement of the same circuits in motor imagery tasks, in the absence of overt responses. The present study aimed to test whether imagined performance of a stop-signal task produces a similar pattern of motor-related EEG activity than that observed during real performance. To this end, mu and beta event-related desynchronization (ERD) and the Lateralized Readiness Potential (LRP) were analyzed. The study also aimed to clarify the functional significance of the Stop-N2 and Stop-P3 ERP components, which were also obtained during both real and imagined performance. The results showed a common pattern of brain electrical activity, and with a similar time course, during covert performance and overt execution of the stop-signal task: presence of LRP and Stop-P3 in the imagined condition and identical LRP onset, and similar mu and beta ERD temporal windows for both conditions. These findings suggest that a similar inhibitory network may be activated during both overt and covert execution of the task. Therefore, motor imagery may be useful to improve inhibitory skills and to develop new communicating systems for Brain Computer Interface (BCI) devices based on inhibitory signals.